The Role of Deep Learning in Elementary Education: Pedagogical Insights from a Literature Study - Budhiarti, Yuli; Mytra, Prima; Slow, Lilian (Jurnal Pedagogi dan Inovasi Pendidikan, 2025)
This study aims to explore the concept and implementation of deep learning at the elementary school level through a literature-based approach grounded in contemporary pedagogical theories and practices. The research employs a descriptive qualitative methodology, drawing on a systematic review of literature from scientific journals, academic books, policy reports, and both national and international research studies. The analysis was conducted thematically by categorizing findings into conceptual foundations, implementation models, mental actions, the role of teachers, and supporting pedagogical principles such as active engagement, differentiation, and positive reinforcement. The results of the review indicate that deep learning emphasizes students’ cognitive engagement through higher-order mental activities such as analysis, synthesis, evaluation, and critical reflection on information. This approach is rooted in constructivist theories (Piaget, Vygotsky), the theory of meaningful learning (Ausubel), and the concept of mindful education (Langer), which together form a robust theoretical basis for facilitating meaningful and contextual learning. Teachers play a pivotal role as facilitators in creating inclusive and dialogic learning environments that enable students to actively explore and engage in social collaboration to construct deep understanding. In conclusion, the integration of deep learning into elementary education has the potential to enhance the quality of teaching and learning processes by fostering critical and creative thinking patterns, while also preparing learners to be adaptive and reflective. These findings provide a conceptual and practical foundation for developing future pedagogical strategies in response to the challenges of 21st-century education.